Analisis Perbedaan Biaya Satuan Sectio Caesarea Tanpa Penyulit dengan Tarif INA-CBGs di Rumah Sakit Swasta Tipe D (X) di Ternate Tahun 2022 - Hani, Ummu, MARS; Soewondo, Prastuti (UI Scholars Hub, 2025)
Cesarean section unit cost is an important component for hospital’s management to implement strategic efficiency steps in the future, especially for Rumah Sakit X which 90% of patients are Jaminan Kesehatan Nasional’s participant. Geographically, this hospital is one of hospitals which serve delivery and labor services in Ternate Island that can accommodate references from nearby islands. This resulting in high caesarean section rate, 55 % of all deliveries. The low JKN rate for caesarean section forced management to know the detailed cost component, so the efficiency strategies and the continuity of hospital services could be more increased. This research through quantitative strategy, processing caesarean section patients’ secunder data, interviewing staff, and looking through hospital’s financial statements. We analyzed every Caesarean sections in 2022 using Activity Based Costing. The total cost for caesarean section is 6.659.302 IDR. The difference from INA-CBGs are 1.569.376 IDR for 3rd class, 754.976 IDR for 2nd class, and 59.524 IDR for 1st class. Efficiency efforts than had been done was reducing the length of stay and using consumables with lower price. Expansion of caesarean section was suggested with cooperation with midwives and first degree health care in order to minimize the hospital referrence.